The Effects of Augmented Reality in a 7th-Grade Science Lesson on Students' Academic Achievement and Motivation - Hasan Hüseyin Kul; Asiye Berber (Journal of Science Learning, 2022)
This study examines the effects of a seventh-grade science course supported by augmented reality technologies on students' academic achievement on elements and compounds, their motivation towards the science course, and their motivation toward the augmented reality materials used. The study was conducted with the quasi-experimental design of the quantitative research method. The research sample consists of 50 seventh-grade students, 25 in the experimental group and 25 in the control group, studying in a public school. As data collection tools, academic achievement tests, motivation scale for learning science, and motivation scale for the materials used were utilized. In addition, the collected data were analyzed with the SPSS 24.0 program. As a consequence of the research, it was discovered that augmented reality technologies boosted students' academic success and motivation toward science learning (p0.001). In addition, students' motivation toward augmented reality materials was also found to be high.